2019
DOI: 10.1074/jbc.ra118.005663
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of methionine residues in human apolipoprotein A-I generates a potent pro-inflammatory molecule

Abstract: Amyloid deposits of apolipoprotein A-I (apoA-I) and inflammation are common in atherosclerotic arteries. In this study, we investigated the interplay between oxidation of apoA-I methionine residues (Met(O)-ApoA-I), a known amyloidogenic modification of apoA-I, and the inflammatory response of immune cells. Soluble pre-fibrillar Met(O)-ApoA-I, but not apoA-I, induced intracellular accumulation of pro-interleukin (IL)-1␤ and secretion of the pro-inflammatory cytokines tumor necrosis factor ␣ (TNF␣) and IL-6 in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…However, while research in atherosclerotic disease has indicated that the oxidation of methionine residues in human apoA-I can serve as a potent inflammasome activator [172], no clinical studies have definitively established a direct link between oxidized HDL components and the activation of the NLRP3 inflammasome signaling pathway during MI. Therefore, it is imperative to conduct further investigations to explore the specific pro-inflammatory mechanisms arising from oxidized HDL components.…”
Section: Oxidation In Hdl Components During MI and Inflammasome Activ...mentioning
confidence: 99%
“…However, while research in atherosclerotic disease has indicated that the oxidation of methionine residues in human apoA-I can serve as a potent inflammasome activator [172], no clinical studies have definitively established a direct link between oxidized HDL components and the activation of the NLRP3 inflammasome signaling pathway during MI. Therefore, it is imperative to conduct further investigations to explore the specific pro-inflammatory mechanisms arising from oxidized HDL components.…”
Section: Oxidation In Hdl Components During MI and Inflammasome Activ...mentioning
confidence: 99%
“…Scavenger receptor class B type I (SR-BI) is overexpressed in tumor cells and participates in the cholesterol metabolism of tumor cells [ 74 , 75 ]. ApoA-I can specifically target SR-BI and mediate the anti-inflammatory ability of macrophages by regulating the production of cytokines in macrophages [ 76 ]. Therefore, SR-BI can be used as a specific target for the treatment of common tumors such as breast cancer, ovarian cancer and prostate cancer [ 77 , 78 ] ( Figure 3 B).…”
Section: Reconstituted High-density Lipoprotein (Rhdl)mentioning
confidence: 99%
“…While Met(O)-ApoA-I monomers increase CEC, they also initiate amyloidogenesis which ultimately results in the sequestration and inactivation of otherwise antiatherogenic and HDL-forming ApoA-I [54]. Met86(O)-ApoA-I and Met148(O)-ApoA-I have been reported to maintain their cholesterol-accepting capacity while strongly inducing pro-inflammatory cytokine production in surrounding immune cells [55], contributing to atherosclerotic disease progression. MPO overexpression in atherosclerotic lesions is also known to result in chlorination and nitration of ApoA-I tyrosine residues.…”
Section: Oxidationmentioning
confidence: 99%